Effect of oocyte dysmorphisms on intracytoplasmic sperm injection cycle outcomes in normal ovarian responders. Issue 12 (30th September 2015) - Ashrafi, Mahnaz; Karimian, Leila; Eftekhari‐Yazdi, Poopak; Hasani, Fatemeh; Arabipoor, Arezoo; Bahmanabadi, Akram; Akhond, Mohammad Reza
Abstract: Aim: The aim of this study was to identify the influence of oocyte dysmorphisms on clinical outcomes after intracytoplasmic sperm injection cycle in normal responders. Material and Methods: In the prospective study, morphology of 1999 metaphase II oocytes retrieved from 316 intracytoplasmic sperm injection cycles was evaluated from March 2011 to March 2013 at Royan Institute. Controlled ovarian stimulation was performed by long standard agonist protocol. Oocyte morphology was assessed before sperm injection by one embryologist. The associations between fertilization rate, embryo quality and the independent variables were analyzed using odds ratio (OR) calculated with unconditional logistic regression test. Results: From all retrieved oocytes, 1543 (77.1%) showed at least one morphologic aberration. Presence of cytoplasmic vacuoles and high cytoplasmic viscosity were associated with a significant decrease in the fertilization rate (OR: 0.5; P  = 0.004 and OR: 0.6; P  = 0.03, respectively). The results showed that oocyte morphology did not affect embryo quality. The number of gonadotrophin injections used showed a direct relation with presence of large perivitelline space. No significant difference was observed among four groups (women with total normal morphologic oocytes [group 1], women with total extracytoplasmic dysmorphic oocytes [group 2], women with total cytoplasmic dysmorphic oocytes [group 3] and women with total oocytes containing multiple dysmorphic features [group 4]) in terms of implantation and clinical pregnancy rates. Conclusions: Metaphase II oocyte morphology had minor impacts on fertilization rate, pronuclear morphology and embryo quality in women with normal ovarian response.